2014
DOI: 10.1155/2014/458601
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Mechanisms and Disrupted Cytoskeleton in the Diphenyl Ditelluride Neurotoxicity

Abstract: Evidence from our group supports that diphenyl ditelluride (PhTe)2 neurotoxicity depends on modulation of signaling pathways initiated at the plasma membrane. The (PhTe)2-evoked signal is transduced downstream of voltage-dependent Ca2+ channels (VDCC), N-methyl-D-aspartate receptors (NMDA), or metabotropic glutamate receptors activation via different kinase pathways (protein kinase A, phospholipase C/protein kinase C, mitogen-activated protein kinases (MAPKs), and Akt signaling pathway). Among the most relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 230 publications
(268 reference statements)
0
6
0
1
Order By: Relevance
“…Many organotellurium compounds, as well as simple tellurium salts, often show considerable activity against pathogenic organisms, in some instances even re-sensitizing drug resistant strains against common antibiotics [ 34 ]. Yet tellurium is also a fairly toxic element per se, and any application, even a topical one, clearly requires further investigations to exclude any unwanted side effects [ 35 , 36 ]. The particular particulate structure may actually be a benefit rather than drawback in this context, as it almost rules out the kind of systemic uptake and distribution characteristic of soluble, toxic organotellurium compounds and, at the same time, may provide a slowly releasing system for certain reactive tellurium species (RTeS).…”
Section: Discussionmentioning
confidence: 99%
“…Many organotellurium compounds, as well as simple tellurium salts, often show considerable activity against pathogenic organisms, in some instances even re-sensitizing drug resistant strains against common antibiotics [ 34 ]. Yet tellurium is also a fairly toxic element per se, and any application, even a topical one, clearly requires further investigations to exclude any unwanted side effects [ 35 , 36 ]. The particular particulate structure may actually be a benefit rather than drawback in this context, as it almost rules out the kind of systemic uptake and distribution characteristic of soluble, toxic organotellurium compounds and, at the same time, may provide a slowly releasing system for certain reactive tellurium species (RTeS).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the toxicological properties of (PhTe) 2 have been investigated in in vivo and in vitro experimental models. Especially in liver, acute and/or chronic intoxication have been reported to increase the organ-to-body weight ratio, inhibit δ -ALA-D enzyme, increase thiobarbituric acid reactive substances, decrease nonprotein SH levels, and modify antioxidant enzymes activities in rodents [ 17 , 19 , 29 , 37 ]. In morphological terms, herein we observed that the liver of animals exposed to (PhTe) 2 (10 and 50 μ mol/kg), for few days, contained hepatocytes with extensive cytoplasmic vacuolization, hydropic degeneration (edema), and hyperchromatic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to mechanisms, it has been postulated that the toxic action of Te forms (organic and inorganic) involves their prooxidant potential towards thiol groups from biologically active molecules [ 10 , 14 – 19 ]. In a similar way, accumulating evidence has showed that the compound diphenyl ditelluride ((PhTe) 2 ), an organotellurium used commonly as intermediate in organic synthesis [ 9 ], is toxic to different tissues [ 20 29 ] and inhibits sulfhydryl containing enzymes in vitro and in vivo [ 9 , 16 , 19 ]. Moreover, (PhTe) 2 exposure has been associated with teratogenic, mutagenic, and genotoxic events [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, developmental exposure to (PhTe) 2 is teratogenic and is associated with long-term behavioral and neurochemical changes in rats. Until recently, the general toxicity of (PhTe) 2 was considered to be exclusively related to the oxidation of thiol-containing proteins (for review, see [16]). However, compelling evidence from our laboratory points to an important role played by signaling mechanisms involved in regulating IF phosphorylation/dephosphorylation as target of (PhTe) 2 neurotoxicity.…”
Section: Toxicity Of Diphenyl Ditelluride On the Cytoskeleton Of Neurmentioning
confidence: 99%